Two-band optical gain and ultrabright electroluminescence from colloidal quantum dots at 1000 A cm−2 - Heeyoung Jung; Young-Shin Park; Namyoung Ahn; Jaehoon Lim; Igor Fedin; Clément Livache; Victor I. Klimov (Nature Communications, 2022)
Nonradiative Auger recombination and poor stability of colloidal-quantum-dot solids at high current densities are primary obstacles to the realization of laser diodes based on these materials. Jung et al. achieve the current densities in excess of 1,000 A cm−2, which allows them to boost brightness to ~10 million cd m−2 and to produce strong, two-band optical gain.